Global Trends in Natural Biopolymers in the 21st Century: A Scientometric Review - Sun, Yitao; Bai, Yinping; Yang, Wenlong; Bu, Kangmin; Tanveer, Sikander Khan; Hai, Jiangbo (Frontiers in Chemistry, 2022)
A wealth of published data can provide basic information and guidance for the content of the research field, the changes in the themes that have occurred, and the trends in areas that deserve attention. Since the 21 st century, the research on natural biopolymers has shown a positive growth trend. However, these substantive scientific achievements are not conducive to our rapid grasp of hotspots and insight into the future direction. Therefore, based on 7270 natural biopolymer articles in the Web of Science Core Collection (WOSCC) database, rigorous bibliometric and quantitative visualization analyses were carried out based on mathematical model VOS Viewer and CIteSpace software. The United States is reported to be the most important contributor to research in this field, with numerous publications and active institutions; Polymer Science is the most popular subject category; the mainstream research in this field has been divided into five knowledge structure clusters; since 2015, the number of papers in the field of natural biopolymer research has increased explosively. This study also introduces the Activity Index (AI) and the Attractive Index (AAI) to generate the temporal evolution trajectories of some major countries from 2000 to 22021 and assess their trends and performance.Researchers have mainly engaged in three research directions: medicine, biochemistry, and food science; the research on natural biopolymers should further emphasize the cooperation of transnational disciplines and institutions. Understanding the evolution of objective bibliometric characteristics and research topics can provide a valuable reference for future research. This study can be seen as a microcosm of the field of natural biopolymers, which will help researchers quickly identify their general patterns. Readers can obtain exciting information from rich bibliometric data, which will help different institutions learn from each other and accelerate the diversification of natural biopolymers.